Fragmentos florestais e testes de progênies: opções para a coleta de sementes em espécies arbóreas nativas do Cerrado no Bolsão Sul-Mato-Grossense - Cambuim, José [UNESP] (2017)
The forest fragment and progeny tests, with the function of assisting conservation, rehabilitation of ecological processes and promoting biodiversity conservation, play an important role in the restoration of degraded areas and reduce the negative effects of the destruction of natural environments. This work aimed to know the population structure, spatial distribution and effective size of native tree species present in a cerrado forest fragment, besides estimating the genetic variability in a test of mixed progenies of Myracrodruon urundeuva; Terminalia argentea and Astronium fraxinifolium; from silvicultural characters in Selvíria - MS, with a view to transforming them into an area to subsidize seed collection. In the forest fragment were measured and identified 1187 individuals with DBH ≥ 10 cm, which make up the arboreal forest canopy. In an area of 0,89 ha were sampled, belonging to 60 species distributed in 31 families, with emphasis on the Fabaceae family with 11 species. The Shannon-Weaver index showed a H '= 2,98 nats ind-1, which can be considered as a mean diversity. The species with the highest Import Value Index (IVI) were Copaifera landesdorffii, Diptychandra aurantiaca, Parapiptadenia rigida, Qualea grandiflora, Qualea parviflora, Vochysia tucanorum, Tapirira guianensis, Astronium fraxinifolium, Xylopia aromatica, and Mabea fistulifera. Thus, among the species found with the highest IVI can be classified as potential for the lease of matrix trees to subsidize the collection of seeds. Therefore, they have an effective size that allows the formation of new populations, from the collection of seeds in this area of legal reserve. In the progenies test mixed at 22 years, the high values observed for SOB (M. urundeuva – 88,0%, A. fraxinifolium – 85,9% and T. argentea – 59,6%) indicated a good adaptation of the Species and potential for use in reforestation. Estimates of the coefficient of genetic variation ranged from 3,03% to 49,50%, estimating the lowest value obtained for the DAP variable in the three species. The individual heritabilities ranged from low (0,14) for T. argentea, and high (> 0,40) for M. urundeuva and A. fraxinifolium on the DAP character. The sex ratio for both species was biased for males, with the general proportion being 1,5 males for 1 female. The effective population size varied according to the proportion of males and females, and the one that most approached the real value of reproductive individuals was Myracrodruon urundeuva. Therefore, the selection of individuals within progeny tests should not only consider the growth character (DBH), but also on the basis of the sex ratio and the effective population size for its future transformation into a Seedling Seed Orchard. The information obtained from this study is useful for the conservation and genetic improvement of the species, as well as for the selection of potential matrices for environmental restoration, which will be fundamental for ecological restoration in areas of the Bolsão Sul-mato-grossense.